2020
DOI: 10.3390/mi11080740
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Impact Ionization Coefficient of ZnO Based on a p-Si/i-ZnO/n-AZO Avalanche Photodiode

Abstract: The avalanche photodiode is a highly sensitive photon detector with wide applications in optical communication and single photon detection. ZnO is a promising wide band gap material to realize a UV avalanche photodiode (APD). However, the lack of p-type doping, the strong self-compensation effect, and the scarcity of data on the ionization coefficients restrain the development and application of ZnO APD. Furthermore, ZnO APD has been seldom reported before. In this work, we employed a p-Si/i-ZnO/n-AZO structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…39 Similarly, Pradel et al demonstrated that the piezoelectric output was significantly increased by two ZnO layers containing different dopants. 40 The p-Si/ZnO/n-AZO heterostructure was also demonstrated by Li et al 41 In our work, a P-N junction formed between the p-doped Si-substrate and the ZnO NWs could lead to a higher piezoelectric amplitude compared to ZnO/AZO junction, but the present experimental results show the opposite trend. The other factor that could also affect the results is the dimensions of NWs.…”
Section: Discussionsupporting
confidence: 75%
“…39 Similarly, Pradel et al demonstrated that the piezoelectric output was significantly increased by two ZnO layers containing different dopants. 40 The p-Si/ZnO/n-AZO heterostructure was also demonstrated by Li et al 41 In our work, a P-N junction formed between the p-doped Si-substrate and the ZnO NWs could lead to a higher piezoelectric amplitude compared to ZnO/AZO junction, but the present experimental results show the opposite trend. The other factor that could also affect the results is the dimensions of NWs.…”
Section: Discussionsupporting
confidence: 75%
“…This work shows that, by adjusting the C/Si ratio, the quality of the 4H-SiC epilayer can be improved and the performance of the Ni/4H-SiC Schottky detector increased. In their work, G. Li et al evaluate the impact ionization coefficient of electrons in a ZnO layer along the (001) direction [ 12 ]. In order to do it, the authors have investigated p-Si/i-ZnO/n-AZO structures illuminated by a 532 nm laser diode where the electron avalanche multiplication is triggered in the i-ZnO layer whose thickness was varied from 250 to 750 nm.…”
mentioning
confidence: 99%